2015
DOI: 10.1097/ccm.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Critical Care

Abstract: Current critical care fellows may be unprepared to deal with the increasing prevalence of cardiovascular illness in the ICU. This potential educational gap warrants timely attention to ensure that future graduates have the requisite skills necessary to manage these critically ill patients and presents a unique opportunity to develop multidisciplinary partnerships for enhancing training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Third, another reason may be that current non-cardiovascular critical care providers may feel unprepared in the management of complex cardiovascular critical illness in medical ICUs leading to a greater proportion of these patients being managed in the CICU. 10 Fourth, the shift in coding toward primary non-cardiac diagnoses may reflect changes in reimbursement that encourage ‘up-coding’ or shifting of diagnoses toward higher categories of complex conditions. The fact that we found greater rates of co-morbidities despite stable-to-improving risk adjusted outcomes suggests this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, another reason may be that current non-cardiovascular critical care providers may feel unprepared in the management of complex cardiovascular critical illness in medical ICUs leading to a greater proportion of these patients being managed in the CICU. 10 Fourth, the shift in coding toward primary non-cardiac diagnoses may reflect changes in reimbursement that encourage ‘up-coding’ or shifting of diagnoses toward higher categories of complex conditions. The fact that we found greater rates of co-morbidities despite stable-to-improving risk adjusted outcomes suggests this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…79 This latest trend has raised some concern among cardiologists, as caring for these groups of patients may require expertise in critical care and non-cardiac procedures that fall beyond the purview of typical general cardiology training. 6, 10 …”
mentioning
confidence: 99%
“…142 Conversely, although the ICU may be well suited to manage noncardiac organ failure, surveys have reported that ICU trainees may be unprepared to manage cardiovascular illness and to perform common cardiovascular procedures. 148 ICU-based observational studies have reported improved outcomes in a closed unit staffing model. 149 In addition, in the CICU, there is emerging evidence from a before-and-after study that transition from an open low-intensity care model to a closed unit model with care led by a dual-trained cardiologist-intensivist may improve outcomes; however, further studies are required to evaluate the independent influence of staffing and physician training.…”
Section: Cicu Versus Icu Admissionmentioning
confidence: 99%
“…En cambio, las unidades de tipo "cerrado" están dotadas de un equipo médico estable que toma la gran mayoría de las decisiones, más allá de un mayor o menor grado de interacción con el médico tratante. Existe un cuerpo de evidencia importante que favorece al modelo "cerrado", con un equipo médico presente en régimen de 24 horas, en términos de resultados (incluyendo mortalidad), lo que es aplicable tanto a las unidades generales como a las especializadas en el área cardiovascular (11) . Es interesante que esta discusión no se aplicaría en Uruguay, y probablemente en otros países de Latinoamérica, dado que en la mayoría de ellos las unidades de cuidados intensivos se desarrollaron con un modelo "cerrado" desde su origen.…”
Section: Problemas De Organizaciónunclassified
“…Si bien en la literatura científica hay detallada discusión sobre estos temas organizacionales, no se cuestiona la importancia de la existencia de UCIC con médicos cardiólogos participando activamente de la organización y operación de estos centros y se establecen variados esquemas de formación curricular de acuerdo con las diferentes organizaciones y medios académicos (11) . Existe más de un camino para obtener una especialización que contemple la formación en cardiología y en cuidado intensivo, lo que también dependerá de la comunidad médica que se trate y para qué tipo de complejidad de UCIC.…”
Section: Formación Curricularunclassified